2017
DOI: 10.3892/or.2017.5891
|View full text |Cite
|
Sign up to set email alerts
|

Complex analysis of the TP53 tumor suppressor in mantle cell and diffuse large B-cell lymphomas

Abstract: Mutations and deletions of the tumor suppressor TP53 gene are the most frequent genetic alterations detected in human tumors, though they are rather less frequent in lymphomas. However, acquisition of the TP53 mutation was demonstrated to be one of the characteristic markers in mantle cell lymphoma (MCL) and diffuse large B-cell lymphoma (DLBCL) and prognostic value of the TP53 status has been recognized for these diseases. We present the complex analysis of the TP53 aberrations in 57 cases of MCL and 131 case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Inactivation or functional alternation of p53 by genomic loss or modulating mutations are frequently observed in human hematopoietic neoplasias including DLBCLs. Thereby, loss or mutation of p53 correlates with chemo resistance, shorter overall as well as progression free survival 38 . Consequently, the herein observed downregulation in the cell lines indicated a selection of an aggressive clone within the cell line compared to the primary samples.…”
Section: Resultsmentioning
confidence: 99%
“…Inactivation or functional alternation of p53 by genomic loss or modulating mutations are frequently observed in human hematopoietic neoplasias including DLBCLs. Thereby, loss or mutation of p53 correlates with chemo resistance, shorter overall as well as progression free survival 38 . Consequently, the herein observed downregulation in the cell lines indicated a selection of an aggressive clone within the cell line compared to the primary samples.…”
Section: Resultsmentioning
confidence: 99%
“…The authors suggest that patients with MCL should be stratified according to TP53 status, and that patients with TP53 mutations should be considered for experimental frontline trials exploring novel agents. Zlamalikova et al [ 37 ] add significant data to this work. They present the complex analysis of the TP53 aberrations in 57 cases of MCL and 131 cases of DLBCL.…”
Section: New Entities/subtypesmentioning
confidence: 82%
“…However, Greiner et al assessed p53 expression at the protein level in MCL patients, but only reported correlation between TP53 mutations and the patients’ OS 7 . Stefancikova and Zlamalikova et al also were unable to find relevance between expression of p53 protein and MCL prognosis 26 , 27 . Thus, the single antigen expression of p53, Sox11, or Pax5 might not be sufficient to predict MCL prognosis.…”
Section: Discussionmentioning
confidence: 93%